Incorporating digital anorectal examinations for anal cancer screening into routine HIV care for men who have sex with men living with HIV: a prospective cohort study. Issue 12 (5th December 2018) - Ong, Jason J; Walker, Sandra; Grulich, Andrew; Hoy, Jennifer; Read, Tim RH; Bradshaw, Catriona; Chen, Marcus; Garland, Suzanne M; Hillman, Richard; Templeton, David J; Hocking, Jane; Eu, Beng; et al.
Abstract: Introduction: Men who have sex with men (MSM) living with HIV have a high risk of anal cancer, which is often detected at late stages, when morbidity and mortality are high. The objective of this study was to describe the feasibility and challenges to incorporating regular digital anorectal examination (DARE) into routine HIV care for MSM living with HIV, from the perspective of patients, physicians and the health service. Methods: In 2014, we recruited 327 MSM living with HIV, aged 35 and above from one major sexual health centre (n = 187), two high HIV caseload general practices (n = 118) and one tertiary hospital (n = 22) in Melbourne, Australia. Men were followed up for two years and DARE was recommended at baseline, year 1 and year 2. Data were collected regarding patient and physician experience, and health service use. An ordered logit model was used to assess the relationship between sociodemographic factors and the number of DAREs performed. Results: Mean age of men was 51 (SD ± 9) years, 69% were Australian born, 32% current smokers, and mean CD4 was 630 (SD ± 265) cells per mm 3, with no significant differences between clinical sites. Overall, 232 (71%) men received all three DAREs, 71 (22%) received two DAREs, and 24 (7%) had one DARE. Adverse outcomes were rarely reported: anal pain (1.2% of total DAREs), bleeding (0.8%) and not feeling in control of their body during the examination (1.6%). Of 862 DAREs performed, 33 (3.8%) examinations resulted in a referral to a colorectal surgeon. One Stage 1 anal cancer was detected. Conclusion: Incorporation of an early anal cancer detection programme into routine HIV clinical care for MSM living with HIV showed high patient acceptability, uncommon adverse outcomes and specialist referral patterns similar to other cancer screening programmes.